DATA PROTECTION AND PRIVACY CHALLENGES IN NIGERIA: LESSONS FROM OTHER JURISDICTIONS (UCC Law Journal, 2023)
Data protection and privacy challenges are prevailing issues in Nigeria and other developing countries in Africa. The crux of this paper is to examine the extent of the data and privacy challenges existing in Nigeria. Through a comparative analysis, this paper examined the existing provisions of data protection laws in some European countries and those of Nigeria with the aim of revealing the consequence of insufficient legislation to protect data or data users' privacy, the applicability and responsiveness of existing data protection laws in Nigeria, the dearth of legal precedents, the appalling lack of awareness of data privacy rights, and how it tends to handle or manage human rights violations. The paper adopts the doctrinal research method to identify these issues and propose viable solutions by comparatively examining the protection of data in Europe, with a focus on the legal regimes of data protection in the United Kingdom, Germany, and France. The paper concludes that Nigeria requires thorough data protection legislation like that of developed nations to provide effective data protection and a robust enforcement framework.